The Structure of 2,5-Diphenyl-1H-cyclopropabenzene - Paul Müller; Gérald Bernardinelli; Huong Can Godoy-Nguyen Thi (CHIMIA)
The structure of the title compound (1-H), determined by X-ray crystallography, is reported. The molecule is planar and geometry of the «benzocyclopropene» moiety is the same as that for the parent compound (2-H). The lateral cyclopropene bond lenghts vary with the substituents at C(1) in both 1 and 2.